Reproductive cycles of teiid lizards in Amazonian savanna - Magnusson, William Ernest (Journal of Herpetology, 1987)
Ameiva ameiva, Cnemidophorus lemniscatus and Kentropyx striatus reproduce seasonally in savanna near Alter do Chao, Brazil. Most egg deposition occurs during the wet season. Relative fat-body size varies little throughout the year. There is no apparent correlation between fat-body size and gonad development. -Author
Keywords: Lizard; Reproductive Cycle; Savanna; Alter Do Chao; Amazonia; South America; Ameiva Ameiva; Ameiva Ameiva; Cnemidophorus Lemniscatus; Cnemidophorus Lemniscatus; Kentropyx; Kentropyx Striatus; Squamata; Teiidae; Teiidae